The Impact of Business Transformation in Improving Operational Performance at PT Telkom Witel Sulbagteng - Rian, Rian; Syamsuddin, Syamsuddin; Asngadi, Asngadi; Dwiwijaya, Kadek Agus (SIMAK, 2025)
This research was conducted to determine the impact of business transformation on improving operational performance at PT Telkom Witel Sulbagteng. The qualitative approach is based on a literature review of business transformation, Enterprise Resource Planning (ERP) systems, and operational performance. Microsoft Excel was used as the analysis tool. The study population consists of employees at PT Telkom Witel Sulbagteng. The results of this study indicate that service quality based on interviews, the top priority in improving operational performance is focusing on more responsive and high-quality customer services, such as enhancing customer trust through technologies such as cloud computing and big data, operational optimization is the second priority, although it faces challenges in coordination and service distribution, service diversification is critically important to meet changing market demands, making it a high priority, and human resource development does not dominate due to challenges in human resource capacity.